2002
DOI: 10.1053/jhsu.2002.35074
|View full text |Cite
|
Sign up to set email alerts
|

Enabling meta-analysis in systematic reviews on carpal tunnel syndrome

Abstract: Possible solutions to the problems of clinical heterogeneity of outcome measures and inadequate reporting of results for randomized controlled trials (RCTs) on carpal tunnel syndrome (CTS) are presented. Meta-analysis was impeded by these problems in 2 systematic reviews concerning conservative and surgical treatment options for CTS. A solution to the problem of inadequate data presentation is to add explicit information on minimal requirements with regard to data presentation to guidelines for the reporting o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 40 publications
0
13
0
1
Order By: Relevance
“…A problem in comparing the results of surgery is the number of different outcome measures used to report results. 18 Both Amadio et al 19 and Katz et al 4 have found that subjective outcome scores were more sensitive to change than traditional physical measures and that physical examination had little usefulness for predicting postsurgical functional limitations, symptoms, or satisfaction. Improvements have been reported in general outcomes scores such as the Arthritis Impact Measurement Scale and the ShortForm 36; however, these changes were not as great as those seen with the condition-specific Symptom Severity Score.…”
Section: Discussionmentioning
confidence: 99%
“…A problem in comparing the results of surgery is the number of different outcome measures used to report results. 18 Both Amadio et al 19 and Katz et al 4 have found that subjective outcome scores were more sensitive to change than traditional physical measures and that physical examination had little usefulness for predicting postsurgical functional limitations, symptoms, or satisfaction. Improvements have been reported in general outcomes scores such as the Arthritis Impact Measurement Scale and the ShortForm 36; however, these changes were not as great as those seen with the condition-specific Symptom Severity Score.…”
Section: Discussionmentioning
confidence: 99%
“…Conservative treatment of CTS also accounts for a large proportion of resources and includes splinting, nerve gliding, ultrasound and carpal bone mobilisation[2]. Whilst the reported success rates of carpal tunnel release range from 70 to 90 percent there is little agreement on how results should be evaluated[4]. …”
Section: Introductionmentioning
confidence: 99%
“…Outcomes from carpal tunnel release have been assessed in many different ways including objective nerve conduction studies, clinical measures of sensibility, muscle function and dexterity, patient-reported symptoms and perceived function and the impact on daily activity, work and leisure. It has also been noted, that there is a lack of consensus among clinicians over what constitutes the most reliable, valid and responsive instruments to evaluate outcomes in carpal tunnel syndrome[4,6]. …”
Section: Introductionmentioning
confidence: 99%
“…The number of meta-analyses conducted in hand surgery has been modest to date. This may be the result of a lack of common outcomes or incompatible data, as found by Gerritsen et al 37 In the hand surgery field, meta-analysis is still in the infancy stage because high-quality clinical trials that provide robust data that can be pooled are still lacking. When performed appropriately, however, a meta-analysis can lend evidence to many of the difficult decisions we make in our daily practice.…”
Section: Report the Resultsmentioning
confidence: 99%